Formación docente y saberes locales: una mirada desde la ruralidad. Venezuela - Jesús Núñez (Revista Electrónica Educare)
Teacher's education in Latin American countries is surrounded by complexity and contradiction. Teachers reproduce continuously and mostly unconsciously modern knowledge inherited of western culture. However, the context of educational activity exhibits great richness, which has been accumulated from the wisdom of people ignored in the curricula of formal educational programs. The article proposes the urgent need of giving social and cultural relevance to the knowledge that is being taught in schools. Two key aspects are proposed: first, giving academic status to local knowledge, powered by the emerging episteme of the crisis of modernity; and second, the necessity of establishing an intercultural dialog between local and universal knowledge, in order to take advantage of its strengths, assuming a synergic posture about human knowledge.